Task Migration for Fault-Tolerant FlexRay Networks - Klobedanz, Kay; Defo, Gilles B.; Zabel, Henning; Müller, Wolfgang; Zhi, Yuan
In this paper we present new concepts to resolve ECU (Electronic Control Unit) failures in FlexRay networks. Our approach extends the FlexRay bus schedule by redundant slots with modifications in the communication and slot assignment. We introduce additional backup nodes to replace faulty nodes. To reduce the required memory resources of the backup nodes, we distribute redundant tasks over different nodes and propose the migration of tasks to the backup node at runtime. We investigate different solutions to migrate the redundant tasks to the backup node by time-triggered and event-triggered transmissions.
Keywords: Faulty Node Static Segment Slot Assignment Task Migration Communication Controller